Visual subsetting, conversion and complex query exploitation in large spatio-temporal databases. (April 2018) - Sharma, Sugam; Tim, Udoyara Sunday; Gadia, Shashi
Abstract: In recent years, large amounts of multidimensional data are being generated at a rapid pace, creating the need to: develop appropriate tools for visual data analytics and for enhancing accessibility and discoverability of the data; and new algorithms and methods for seamless integration, manipulation and interactive visualization of data. We describe an interactive tool and technique for data mining and visualization, called SubVizCon that integrates advanced concepts for spatio-temporal databases with interactive visualization capabilities of the geographic information system software. More specifically, we illustrate the development and implementation of the SubVizCon framework, which integrates geospatial data analysis, feature extraction, and visualization functions in ArcGIS with the advanced subsetting and querying functions of the Parametric Database Model. The seamless integration and interoperability of these software tools within SubVizCon framework enables users to not only visualize large amounts of data but also discover spatio-temporal patterns that might otherwise remain hidden.